Health Management of Diabetes Mellitus Patients in the Work Area Health Center Meskom Subdistrict Bengkalis - Mira Andayani; Suci Amin; Dilgu Meri; Rifa Yanti (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Diabetes mellitus is disease chronic many​ occurs throughout the world. Prevalence disease this Keep going increased, with 8.5% of adults (equivalent to with 422 million people) suffering from Diabetes Mellitus at the global level. Research this aiming for identify management health of Diabetes Mellitus patients in the work area Health Center Meskom. Research this use method studies case with design descriptive. Research results show that 8 respondents (40%) did activity sports, while 12 respondents (60%) did not exercise. As many as 7 respondents (35%) routinely monitor blood sugar levels, while 13 respondents (65%) did not do monitoring. Respondents who regulate pattern Eat totaling 9 people (45%), while 11 respondents (55%) did not arrange pattern eating. As for 8 respondents (40%) running management health, while 12 respondents (60%) did not do it. Management health in Diabetes Mellitus patients aiming For control blood sugar levels, preventing complications term length, and increase quality life patient. Output study this designed in form article scientific. Research results show that good blood sugar control, including​ monitoring level glucose regularly, can lower risk complications like retinopathy, neuropathy, and disease cardiovascular. Optimal management involves combination use drugs, patterns controlled eating, as well as sport in a way regular.